2018
DOI: 10.1029/2017jf004374
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Energy Analysis as Generated by Impact and Fragmentation of Single‐Block Experimental Rockfalls

Abstract: The analysis of seismic signals obtained from near‐source triaxial accelerometer recordings of two sets of single‐block rockfall experiments is presented. The tests were carried out under controlled conditions in two quarries in northeastern Spain; in the first test (Foj limestone quarry, Barcelona), 30 blocks were released with masses ranging between 475 and 11,480 kg. The second test (Ponderosa andesite quarry, Tarragona) consisted of the release of 44 blocks with masses from 466 to 13,581 kg. An acceleromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 62 publications
(159 reference statements)
3
44
0
Order By: Relevance
“…Hibert et al () inferred single block mass and velocity from local seismic records with a fair accuracy (median ratio between calculated and measured velocity of 0.2). In contrast, Saló et al () did not find a correlation between kinetic parameters of the blocks and measured seismic energies. All these studies highlight the large uncertainties on rockfall properties (volume, velocity, location, etc.)…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Hibert et al () inferred single block mass and velocity from local seismic records with a fair accuracy (median ratio between calculated and measured velocity of 0.2). In contrast, Saló et al () did not find a correlation between kinetic parameters of the blocks and measured seismic energies. All these studies highlight the large uncertainties on rockfall properties (volume, velocity, location, etc.)…”
Section: Introductionmentioning
confidence: 84%
“…These studies allowed relating the most energetic seismic phases to boulder impacts after a free fall and showed that impacts were characterized by waves packets with frequency contents over the range 1–50 Hz. Controlled releases of single blocks in a marl gully (Hibert et al, ) or in quarries (Saló et al, ) explored seismic amplitude and energy in relation to the kinetics of block impacts. Hibert et al () inferred single block mass and velocity from local seismic records with a fair accuracy (median ratio between calculated and measured velocity of 0.2).…”
Section: Introductionmentioning
confidence: 99%
“…From direct observation of deposit orthophotos of experiments, we can see that the blocks fractured and fragmented into numerous fragments, leading to energy redistribution and cover area variation. Specifically, the fragmentation process will affect the number, magnitude, and intensity of falling rock blocks, eventually affecting rock fragment trajectories and runout, as well as the destructive potential (Agliardi & Crosta, 2003; Jaboyedoff et al, 2005; Corominas et al, 2012; Ruiz‐Carulla et al, 2017; Saló et al, 2018). Therefore, the fragmentation process is fundamental for rockfall analysis.…”
Section: Discussionmentioning
confidence: 99%
“…If we consider the inclined slab as an acceleration stage that allows jointed analog blocks to accumulate speed, these slab experiments can simply describe the rockfall processes in which rock masses impact at high speeds onto the slope foot and are deposited on the horizontal ground near the slope foot (Sanders et al, 2013; Ruiz‐Carulla et al, 2017; Saló et al, 2018). However, if we consider the inclined slab as a sliding surface, based on the classification of landslides in Hutchinson (1998), the slab experiments are all translational slides, which are very common in natural rockslides (Crosta et al, 2017, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the collapses in Niedźwiedzia Cave, which are characteristic not only of the ceiling and walls but also of the floor, may suggest that they are earthquake‐triggered. Importantly, the horizontal acceleration required to break most of the speleothems in Niedźwiedzia Cave (see Figure 6) is comparable to that produced by an earthquake, as they are too high to be produced by block collapse, which does not exceed 1 m/s 2 (Saló et al., 2018). Consequently, we interpret that at least some of the collapses in Niedźwiedzia Cave are earthquake‐induced.…”
Section: Discussion—cave Damage Causesmentioning
confidence: 99%